Ethics and medicine: Jehovah’s Witnesses and the new blood transfusion rules - D. Knapp van Bogaert; G.A. Ogunbanjo (South African Family Practice)
It is against the doctrine of The Watchtower and Bible Tract Society for their followers, the Jehovah’s Witnesses, to accept blood transfusions. For this reason, this topic remains a critical issue in medical practice and ethics. Few patients can survive a haemoglobin level of less than 5 g per decilitre without transfusion. In the medical field, Jehovah’s Witnesses are widely known for their prohibition against the receipt of blood transfusions. The Watchtower Bible and Tract Society, as the church’s legislating body introduced the policy on refusal of blood in 1945, stating that blood transfusion defies divine precepts. This article reviews the ethics of blood transfusion in the Jehovah’s witnesses and the new blood transfusion rules in South Africa.